HIGH PERFORMANCE CONCRETE PROPERTIES FOR ROAD CONSTRUCTION IN THE BIG CITY - , В. О. (Municipal economy of cities. Series: «Economy science», 2013)
The results of studies of the properties of concrete in road laying in the summer season. Climatic conditions affect not only the technology of concrete road works, but also on the physical and mechanical properties of concrete. The technology of the device in the cement concrete pavement road conditions heavy traffic in large cities with a software project performance properties of concrete.